A genomic extension to the sequence of HLA‐A*02:13, identified using third‐generation sequencing. (16th August 2019) - Liu, Yi‐Ling; Lucas, Jonathan A. M.; Turner, Thomas R.; Marsh, Steven G. E.; Mayor, Neema P.
Abstract : Pacific Biosciences' SMRT sequencing method was used to extend the sequence of HLA‐A*02:13 .